Investigating the World of Adult Education in Africa - Mejai B.M. Avoseh (Adult Education Research Conference, 2002)
Adult education in contemporary Africa is faced with a range of problems. This paper tries to stimulate some level of debate around these problems and hopes to include adult education in Africa in the global investigation of the world of adult education.